2019
DOI: 10.3892/mmr.2019.10425
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide suppresses the glycolysis of triple negative breast cancer cells partially by targeting the miR‑33a‑5p‑LDHA axis

Abstract: Triple negative breast cancer (TnBc) is one of the most aggressive types of breast cancer and has a poor prognosis. Therefore, the development of novel drugs and understanding the molecular mechanisms that may contribute to the initiation and development of TnBc are urgently required. chidamide, a histone deacetylase inhibitor, has been reported as possessing anti-cancer properties in several cancers, however, the function of chidamide in TnBc remains to be elucidated. The present study revealed that chidamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Some studies have shown that miR-33a-5p plays a role in the biological process of tumor cells, including cell proliferation, differentiation, and apoptosis [ 21 , 22 ]. For example, miR-33a-5p was found to be underexpressed in lung adenocarcinoma, which could directly target the mTOR pathway in vitro or in vivo to increase sensitivity to Celastrol, and improve antitumor effects and inhibit cell proliferation capacity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that miR-33a-5p plays a role in the biological process of tumor cells, including cell proliferation, differentiation, and apoptosis [ 21 , 22 ]. For example, miR-33a-5p was found to be underexpressed in lung adenocarcinoma, which could directly target the mTOR pathway in vitro or in vivo to increase sensitivity to Celastrol, and improve antitumor effects and inhibit cell proliferation capacity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Galloflavin induced oxidative stress that, in turn, suppressed cell proliferation of TNBC (MDA-MB-231) cells [ 98 ]. Certain compounds, such as chidamide, inhibited glycolysis via a miRNA-33a-5p-mediated inhibition of LDHA in MDA-MB-231 and BT20 cells ( Figure 1 A) [ 64 ]. It is important to note that several flavonoids manifested anticancer potential via inhibition of the glycolytic enzymes.…”
Section: Glycolytic Pathway Targeted By Classical Anticancer Drugsmentioning
confidence: 99%
“…Chidamide is a benzamide histone deacetylase (HDAC) inhibitor, and it has been marketed in China for the treatment of peripheral T-cell lymphoma (PTCL) since 2015 (11). Chidamide has also been used to treat myeloma, non-small lung cancer types and breast cancer due to its antitumor potency (12)(13)(14). Although the antitumor mechanism of chidamide has been widely investigated, studies examining…”
Section: Introductionmentioning
confidence: 99%